Massive bilateral adrenal mass with adrenal insufficiency: a case report of primary adrenal lymphoma - Çetinkaya Altuntaş, Seher; Avcı, Uğur (The European Research Journal, 2022)
Primary Adrenal Lymphoma (PAL) is extremely rare and usually occurs in men in the 6th-7th decade as bilateral, diffuse large B-cell lymphoma (DLBCL). Here, an 80-year-old patient admitted to the urology outpatient clinic with flank pain and bilateral adrenal mass detected on ultrasound is presented. Positron Emission Tomography-Computed Tomography (PET-CT) was planned for the patient who was referred to the endocrine outpatient clinic. The PET-CT scan revealed lobulated-contoured masses containing necrotic areas with a size of 7.4×5.5×9.8 cm, 19 Hounsfield Unit (HU), and SUVmax value of 23.9 the right adrenal, and with the size of 8.4×8.7×10.8 cm, 28 HU, SUVmax value of 27.3 in the left adrenal. These masses were reported to be not compatible with metastasis and suggested a tumor of the adrenal origin or bilateral adrenocortical carcinoma. In laboratory tests, since Adrenocorticotropic hormone level 291-592 pg/mL (high) and Cortisol level was 7.5-9.5 mcg/dL (low), bilateral adrenalectomy was performed considering adrenocortical cancer primarily. Diffuse large B cell lymphoma was determined as the result of the pathology. Postoperative hydrocortisone and fludrocortisone treatment was initiated for the patient immediately. The patient was transferred to the hematology inpatient clinic to receive Rituximab, Cyclophosphamide, Doxorubicin, Vincristine, and Prednisolone chemotherapy. In this case report, we aimed to emphasize that the differential diagnosis should be made well in massive bilateral adrenal masses. Although the diagnosis is challenging, clinicians should be alert in diagnosing lymphoma in bilateral, massive adrenal masses with adrenal insufficiency. Since this disease’s prognosis is poor and aggressive, a histopathological diagnosis should be obtained, and treatment should be initiated as soon as possible.